Separation, Purification, and Activity Analysis of Angiotensin Converting Enzyme Inhibitory Peptides in Enzymatically Hydrolyzed Egg Yolk of Chinese Soft-Shelled Turtle - LIU Huayu, LIAO Pengying, ZHANG Tianfeng, ZHANG Xinrui, DENG Yunning, LI Yaohua, WEI Jinrui, CHEN Jun (Shipin Kexue)
Angiotensin converting enzyme (ACE) inhibitory peptides were separated and purified from an enzymatic hydrolysate of egg yolk from Chinese soft-shelled turtle (Pelodiscus sinensis) by sequential ultrafiltration and gel filtration chromatography. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was utilized for the identification of the active peptides, and bioinformatics tools were utilized for activity evaluation. The peptides with strong ACE inhibitory activity were synthesized and verified, and molecular docking was used to analyze the interaction between the active peptides and ACE. The results showed that the hydrolysis degree of soft-shelled turtle egg yolk by bromelain was (17.70 ± 0.34)%, and the half maximal inhibitory concentration (IC50) of ACE inhibitory activity was (0.210 ± 0.019) mg/mL. Altogether, 36 peptides were identified from fraction F3 with ACE inhibitory activity. Six peptides with higher activity scores were selected for synthesis and activity verification, among which peptides YNGIWPRD and ASDILPKK exhibited strong ACE inhibitory activities with IC50 of (0.019 00 ± 0.000 36) and (0.170 0 ± 0.001 3) mg/mL, respectively. The molecular docking results showed that both peptides bounded to ACE tightly through multiple hydrogen bonds. In conclusion, two new ACE inhibitory peptides were selected from the egg yolk of Chinese soft-shelled turtle.